New Insights into the Reaction Capabilities of Ionic Organic Bases in Cu‐Catalyzed Amination. Issue 9 (13th February 2019) - Lo, Quintin A.; Sale, David; Braddock, D. Christopher; Davies, Robert P.
Abstract : The application of ionic organic bases in the copper‐catalyzed amination reaction (Ullmann reaction) has been studied at room temperature, with sub‐mol‐% catalyst loadings, and with more challenging amines at elevated temperatures. The cation present in the base has been shown to have little effect on the reaction at standard catalyst and ancillary ligand loadings, whereas the choice of anion is crucial for good reactivity. A substrate scope carried out at room temperature with the best performing bases, TBAM and TBPM, showed both bases to be highly effective under these mild reaction conditions. Moreover, under sub‐mol % catalyst loadings and room temperature conditions, TBPM gave good to excellent yields for a number of different amines and functionalized aryl iodides (14 examples). However, reactions involving more challenging amines gave little or no yield. By using more forceful conditions (120 °C) moderate to excellent yields of cross‐coupled products containing more challenging amines was achievable using TBPM and to a lesser extent with TBAM. As part of this work a study on the stability of the organic bases at 120 °C was undertaken. TBAM is shown to decompose to give n Bu3 N and mono‐butylmalonate at higher temperatures, and this can be correlated to a decrease in performance in the coupling reaction. The phosphonium cations in TBPM did not undergo analogous reactivity but were shown instead to experience some degree of deprotonation at the α‐CH2 to generate phosphonium ylides. This however did not lead to a significantly degradation in the activity of the TBPM in the cross‐coupling reaction. Abstract : Room‐temperature sub‐mol % Ullmann amination has been realized, promoted by the organic ionic base TBPM (14 examples). In addition, the stability and application of ammonium and phosphonium based organic ionic bases at higher temperatures was investigated, leading to a new protocol for the activation of structurally complex amines.